Hessian Fly (Diptera: Cecidomyiidae) Biology and Management in Wheat. (1st May 2018) - Schmid, Ryan B; Knutson, Allen; Giles, Kristopher L; McCornack, Brian P
Abstract: The Hessian fly, Mayetiola destructor (Say) (Diptera: Cecidomyiidae), is a major pest of wheat ( Triticum spp. L.), reducing yields in many wheat producing countries around the world. The most commonly practiced and effective management techniques to control Hessian fly infestations are use of resistant wheat cultivars, adherence to optimum planting dates, destruction of volunteer wheat or 'green bridges', and insecticides. However, insecticide applications strictly for Hessian fly control is limited, owing to the temporality of seed treatments (~30 d), and associated cost and difficult timing of foliar applications. Adherence to optimum planting dates and destruction of volunteer wheat can also reduce the risk of infestation from other economically important wheat pests, e.g., aphids, fall armyworm ( Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae)), and wheat curl mite ( Aceria tosichella Keifer (Acari: Eriophyidae)). This highlights that Hessian fly control tactics are more effective when used in an integrated pest management (IPM) program. A shortcoming of the current Hessian fly IPM program is the absence of reliable sampling methods for estimating the risk of Hessian fly damage and economic treatment thresholds. Instead management practices are used as either a preventative measure or in response to damage from the previous season. To ensure the use of the management practices is justified, pest detection surveillance strategies need to be advanced and/or developed in conjunction with economic thresholds, to help producers implement Hessian fly IPM programs.